EFEKTIVITAS SEMANGGI AIR (MARSILEA CRENATA) TERHADAP KADAR TSS PADA FITOREMEDIASI LIMBAH CAIR - Hanasari Faida Pranama; Devany England Filany, Aulia Widiawati Fitriana Dewi, Jian Tikasari, Andien Narita Putri Warisman, F (CV. ADIBA AISHA AMIRA, 2023)
In Indonesia, the majority of small and medium enterprises do not have a good wastewater treatment system. This condition is very detrimental considering that wastewater that cannot be handled can pollute the environment. Industrial waste can be overcome by using the phytoremediation method, for example the use of water clover plants that have been planted in liquid waste can be a phytoremediator medium for the heavy metal Pb in industrial wastewater. The method used is a literature study with Indonesian language research journals in 2013-2023. An analytical research design with supporting data related to phytoremediation in water clover (Marsilea crenata) in journal searches with the help of the internet. Search keywords related to phytoremediation and water clover plants. The keyword